Workshop Pemanfaatan Digital Marketing dalam Pemasaran Bank Sampah - Fenilinas Adi Artanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Waste banks are one solution in overcoming environmental problems, especially in organized waste management. However, the lack of information and education about the importance of waste banks in society is a major challenge in managing waste banks. This activity aims to increase community participation in strengthening the waste bank movement by utilizing digital marketing. This activity provides a digital marketing workshop which provides training on marketing strategies through digital media and also creating social media content. In this case, Instagram social media is used as the main platform for disseminating waste bank information. Participants are taught how to create content in the form of educational content, informational content and creative content (out of the box) that can attract public attention and increase public awareness about waste banks. The result of this activity is an increase in the readiness of waste bank managers to utilize Instagram media as a suggestion for more effective information dissemination, by optimizing educational content, informational content and creative content (out of the box). This activity is expected to be able to support waste banks in managing waste more responsibly and increase community participation in the waste bank program.